2020
DOI: 10.1063/5.0022208
|View full text |Cite
|
Sign up to set email alerts
|

Plasmas generated by electron beam passing through diamond window

Abstract: In this paper, we report the generation of Ar plasmas by using an electron beam passing through a diamond window. It is observed that plasma brightness varies with the electron beam energy and the duty cycle. The transmission properties of the electrons in a 5-μm-thick diamond film are investigated by both experiments and Monte Carlo simulation. The measured transmittance of the electron beam increases from 20% to 80% by increasing the incident energy of the electron beam on the diamond window from 32.5 keV to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The continuous electrons emitted from the LaB 6 cathode were focused and accelerated by high voltage, and then entered the working chamber through the diamond film window, which has been described in our previous work [9]. The diameter of the electron beam was about 1 mm.…”
Section: Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous electrons emitted from the LaB 6 cathode were focused and accelerated by high voltage, and then entered the working chamber through the diamond film window, which has been described in our previous work [9]. The diameter of the electron beam was about 1 mm.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…Titanium, aluminum and other metal films are widely used as transmission windows for high energy electron beam [2,7]. For lower energy electron beam, it was reported that functional films including ceramic film and diamond film are employed in electron beam plasma sources [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrate that the dust flow can become turbulent, especially at low e-beam currents. The second application is concerned with the full rotation of a PC which keeps its symmetry, irradiated sideways by the e-beam.Plasmas generated by e-beam irradiation are of interest in several areas of applied and fundamental physics spanning from industrial processes such as semiconductor etching used in the fabrication of silicon wafers [32][33][34][35][36] to laboratory and space plasmas [37][38][39][40] . The e-beam is an important tool for the manipulation of dust particles in plasma which can induce dynamics with some unique properties such as sheared, laminar and turbulent dust flows 20 .…”
mentioning
confidence: 99%
“…Plasmas generated by e-beam irradiation are of interest in several areas of applied and fundamental physics spanning from industrial processes such as semiconductor etching used in the fabrication of silicon wafers [32][33][34][35][36] to laboratory and space plasmas [37][38][39][40] . The e-beam is an important tool for the manipulation of dust particles in plasma which can induce dynamics with some unique properties such as sheared, laminar and turbulent dust flows 20 .…”
mentioning
confidence: 99%